Fracture Penis: An Analysis of 26 Cases - G.V.Soundra Pandyan; Ahmed Bakeet Zaharani; Mohammed Al Rashid (The Scientific World Journal)
The aim of this study was to review the pattern of penile fracture occurrence, its clinical presentation, diagnosis, management, and outcome at our center. A retrospective analysis of 26 patients with penile fractures treated at our hospital from January 1997 to January 2005 was carried out. We noted an incidence of 3.5 cases per year, occurring more commonly in unmarried men. Of our study group, 28 episodes of penile fractures occurred in 26 patients. Hospital presentation after trauma varied from 2 h to 21 days. Masturbation was the main initiating causative factor and penile hematoma was the most common clinical finding. Nearly 81% noticed the characteristic click prior to the fracture. Clinical diagnosis was adequate in a majority of the cases. Midshaft fractures with right-sided laterality were more frequent in this series. The tear size ranged from 0.5—2.5 cm with a mean of 1.1 cm. All cases, but one, were treated by surgical repair using absorbable sutures. Out of three cases treated conservatively, two failed to respond and had to be treated surgically. False fracture with dorsal vein tear was present in two cases. Involvement of bilateral corpora was seen in one patient. Infection was the most common early complication, while pain with deviation was the late complication. In our experience, clinical findings are adequate enough to diagnose fracture penis in a majority of cases. Surgical exploration with repair of the tear is recommended both in early and delayed presentations. There was no noticeable relationship to the time of initial presentation or with the size and site of tear to the final outcome.